Exploring the Intersection of Democracy and Islam: Trends, Themes, and Emerging Research in Political Systems and Social Movements - Abdulrohim E-sor; Md. Ishaque (Multicultural Islamic Education Review, 2025)
A bibliometric investigation of the relationship between Islam and democracy in scholarly works produced between 2019 and 2025 is the goal of this project. With an emphasis on Islamism, authoritarianism, and democratic government, the main goal is to uncover important themes, trends, and prominent writers. The theoretical framework examines how political Islam interacts with democratic institutions, particularly in nations with a majority of Muslims, and is centered on the conflict between Islamic beliefs and democratic norms. Bibliometric methods were used in a quantitative way. A Boolean search of the Scopus database was used to gather data, and after applying particular inclusion criteria, 149 documents were found. The analysis made use of Microsoft Excel, VOSViewer, and R/R-Studio for network visualization, document analysis, and citation analysis. The findings demonstrate that Islamism and democracy predominate in the field of study, with an increasing emphasis on authoritarianism and the difficulties in reconciling Islamic principles with democratic ones. Pakistan, Indonesia, and Turkey were noted as major contributors to this discipline. New subjects like social justice, identity politics, and polarization are becoming more and more prominent in the conversation. The study advances our knowledge of the relationship between Islam and democracy and offers scholars and decision-makers insightful information. It also provides a thorough overview of international studies on these subjects, highlighting new developments in political Islam and democracy. This study adds something special to the literature since it is among the first to integrate bibliometric analysis with thematic research on Islamism and democratic government.